Repurposing EGFR Inhibitors for Oral Cancer Pain and Opioid Tolerance - Maria Daniela Santi; Morgan Zhang; Naijiang Liu; Chi T. Viet; Tongxin Xie; Dane D. Jensen; Moran Amit; Huilin Pan; Yi Ye (Pharmaceuticals, 2023)
Oral cancer pain remains a significant public health concern. Despite the development of improved treatments, pain continues to be a debilitating clinical feature of the disease, leading to reduced oral mobility and diminished quality of life. Opioids are the gold standard treatment for moderate-to-severe oral cancer pain; however, chronic opioid administration leads to hyperalgesia, tolerance, and dependence. The aim of this review is to present accumulating evidence that epidermal growth factor receptor (EGFR) signaling, often dysregulated in cancer, is also an emerging signaling pathway critically involved in pain and opioid tolerance. We presented preclinical and clinical data to demonstrate how repurposing EGFR inhibitors typically used for cancer treatment could be an effective pharmacological strategy to treat oral cancer pain and to prevent or delay the development of opioid tolerance. We also propose that EGFR interaction with the µ-opioid receptor and glutamate N-methyl-D-aspartate receptor could be two novel downstream mechanisms contributing to pain and morphine tolerance. Most data presented here support that repurposing EGFR inhibitors as non-opioid analgesics in oral cancer pain is promising and warrants further research.